2001
DOI: 10.1016/s0969-2126(01)00577-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the ADP-Specificity of a Novel Glucokinase from a Hyperthermophilic Archaeon

Abstract: Noticeable points of our study are the first structure of ADP-dependent kinase, the structural similarity to members of the ATP-dependent ribokinase family, its rare nucleotide specificity caused by a shift in nucleotide binding position by one phosphate unit, and identification of the residues that discriminate ADP- and ATP-dependence. The strict conservation of the binding site for the terminal and adjacent phosphate moieties suggests a common ancestral origin of both the ATP- and ADP-dependent kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
114
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 31 publications
4
114
0
Order By: Relevance
“…This fold is similar to the core structure of the ribokinase superfamily (Fig. 2, b and c), which includes ribokinase (22), human adenosine kinase (34), adenosine kinase from Toxoplasma gondii (24), 4-methy-5-␤-hydroxyethylthiazole (THZ) kinase (35), ADP-specificity glucokinase (36), and the recently reported 4-amino-5-hydroxymethyl-2-methylpyrimidine phosphate (HMPP) kinase (25). Despite the structural similarity, the amino acid identity between pyridoxal kinase and any of these kinases is low, and only part of the sequence can be aligned.…”
Section: Resultsmentioning
confidence: 71%
“…This fold is similar to the core structure of the ribokinase superfamily (Fig. 2, b and c), which includes ribokinase (22), human adenosine kinase (34), adenosine kinase from Toxoplasma gondii (24), 4-methy-5-␤-hydroxyethylthiazole (THZ) kinase (35), ADP-specificity glucokinase (36), and the recently reported 4-amino-5-hydroxymethyl-2-methylpyrimidine phosphate (HMPP) kinase (25). Despite the structural similarity, the amino acid identity between pyridoxal kinase and any of these kinases is low, and only part of the sequence can be aligned.…”
Section: Resultsmentioning
confidence: 71%
“…5) (19 -21). It was initially reported that the TlGK structure was the most open conformation because they were able to successfully soak ADP out of the crystal, which indicates the absence of a large conformational change (19). The PhGK structure clearly presented a more open conformation, which led to the suggestion that TlGK had been trapped in the ADP-bound conformation following the removal of the ADP from the crystal (21).…”
Section: Resultsmentioning
confidence: 99%
“…It could be that the ␤-phosphate of ADP is required to fully induce this conformational change. The amine nitrogen of Arg-205 from TlGK is 3.8 Å away from the ␤-phosphate of ADP and may form important interactions that help to stabilize a more closed conformation (19). One other possibility is that for PhPFK both co-factor and substrate are required for the conformational change observed as seen in other structures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations